BER analysis of interference-limited synchronous wireless networks with line-of-sight links - Sirigina, Rajendra Prasad (2021)
The bit error rate (BER) of a Rician-faded and interference-limited synchronous wireless network with binary phase shift keying (BPSK) modulation is investigated. The probability density function (PDF) of the phase of the Rician-faded channel is unwieldy. However, the phase of the Rician-faded channel given the magnitude follows Von Mises distribution. This conditional PDF is exploited to derive an accurate expression for the BER of BPSK-modulated signals with an interference ignorant detector. Moreover, if either the desired signal or the interfering signal is Rayleigh-faded, the BER expression based on the uniform distribution assumption for the phase difference in decision statistic is shown to be accurate.